A two-dimensional fault diagnosis model of induction motors using a gabor filter on segmented images - Uddin, Jia; Islam, Mr. Rashedul; Kim, Jong-Myon; Kim, Cheol-Hong (© 2016 Science and Engineering Research Support Society, 2016)
This article was published in the International Journal of Control and Automation [© 2016 SERSC ] and the definite version is available at :http://dx.doi.org/10.14257/ijca.2016.9.1.02 The Journal's website is at:http://www.sersc.org/journals/IJCA/vol9_no1/2.pdf